Effectiveness of neonatal "near miss" audits in reducing perinatal morbidity and mortality: a systematic review protocol. Issue 3 (7th March 2022) - Medeiros, Poliana; Bailey, Cheryl; Andrews, Christine; Liley, Helen; Pollock, Danielle; Gordon, Adrienne; Flenady, Vicki
ABSTRACT: Objective: This review will assess the effectiveness of neonatal near-miss audits in reducing perinatal mortality and morbidity, as implemented in health care facilities. Introduction: Every year, 2.5 million newborns die and 2.6 million more are stillborn worldwide. While many perinatal deaths are preventable, their reduction has been markedly slower than the decline of maternal or child mortality rates. It is hypothesized that neonatal near miss is part of the spectrum of stillbirth–neonatal death and that auditing these cases might reduce perinatal mortality and morbidity. Inclusion criteria: This review will consider neonatal near-miss audits implemented in health care facilities worldwide. Randomized controlled trials, cluster-randomized trials, quasi-randomized controlled trials, controlled before-and-after studies, interrupted time series, case-control, cohort studies, cross-sectional studies, and case series will be included. Conference abstracts, letters, studies duplicating validation data from previous studies, gray literature, and unpublished studies will be excluded. Methods: Using the JBI guidelines for conducting systematic reviews of effectiveness, the review will search the following electronic bibliographic databases: MEDLINE, Embase, Scopus, CINAHL, LILACS, and SciELO. No publication date or language limits will be imposed. Two independent reviewers will screen titles, abstracts, and full-text studies, assessing methodological quality with the JBI critical appraisal tools. GRADE will be used to assess the confidence in the findings. Covidence will be used for data extraction and management. A meta-analysis will be performed if the selected studies are sufficiently homogeneous. If not, the results will be discussed as a narrative synthesis. Systematic review registration number: PROSPERO (CRD42021224090)